Antioxidant Effects of Roasted Licorice in a Zebrafish Model and Its Mechanisms - Qian Zhou; Shanshan Zhang; Xue Geng; Haiqiang Jiang; Yanpeng Dai; Ping Wang; Min Hua; Qi Gao; Shiyue Lang; Lijing Hou; Dianhua Shi; Meng Zhou (Molecules, 2022)
Licorice (Gan-Cao, licorice) is a natural antioxidant and roasted licorice is the most common processing specification used in traditional Chinese medicine prescriptions. Traditional Chinese medicine theory deems that the honey-roasting process can promote the efficacy of licorice, including tonifying the spleen and augmenting “Qi” (energy). The antioxidant activity and mechanisms underlying roasted licorice have not yet been reported. In this study, we found that roasted licorice could relieve the oxidative stress injury induced by metronidazole (MTZ) and could restrain the production of excessive reactive oxygen species (ROS) induced by 2,2′-azobis (2-methylpropionamidine) dihydrochloride (AAPH) in a zebrafish model. It was further found that roasted licorice could exert its oxidative activity by upregulating the expression of key genes such as heme oxygenase 1 (HO-1), NAD(P)H quinone dehydrogenase 1 (NQO1), glutamate–cysteine ligase modifier subunit (GCLM), and glutamate–cysteine ligase catalytic subunit (GCLC) in the nuclear factor erythroid 2-related factor 2 (NRF2) signaling pathway both in vivo and in vitro. Furthermore, consistent results were obtained showing that rat serum containing roasted licorice was estimated to reduce cell apoptosis induced by H2O2. Then, the UHPLC-Q-Exactive Orbitrap MS analysis results elucidated the chemical composition of rat plasma containing roasted licorice extracts, including ten prototype chemical components and five metabolic components. Among them, six compounds were found to have binding activity with Kelch-like ECH-associated protein 1 (KEAP1), which plays a crucial role in the transcriptional activity of NRF2, using a molecular docking simulation. The results also showed that liquiritigenin had the strongest binding ability with KEAP1. Immunofluorescence further confirmed that liquiritigenin could induce the nuclear translocation of NRF2. In summary, this study provides a better understanding of the antioxidant effect and mechanisms of roasted licorice, and lays a theoretical foundation for the development of a potential antioxidant for use in clinical practice.